Attitude of School Teachers towards the use of Computers in Sundarban Region of West Bengal - Pan, Arnab (Indian Journal of Educational Technology, 2022)
Attitude toward computers is the important criteria of a teacher for computer-aided instruction in the teaching- learning process. The study tried to investigate the teacher’s attitude towards computers with respect to gender, teaching experience and subject groups. 300 teachers are taken as sample through random sampling from secondary schools of Sundarbans region of North 24 Pgs and South 24 Pgs districts of West Bengal. Computer attitudes scale of Khatoon and Sharma (2011) is used for data collection and collected data are analyzed through t-test and one way ANOVA. The finding indicates that male teachers have a higher computer attitude than female counterparts. In regarding teaching experience above 20 years experience teachers shows neutral computer attitude while below 10 years and between 10-20 years experience teachers differ significantly from above 20 years experience teachers in their attitude toward computer. All subject groups’ teachers have a positive computer attitude. Science teachers have a comparatively higher altitude than other groups. The study helps to understand the computer attitude of school teachers and helps the educational administrator to take necessary steps regarding technology introduction in the school educational system.